2007
DOI: 10.1128/mcb.01826-06
|View full text |Cite
|
Sign up to set email alerts
|

A Triple Helix within a Pseudoknot Is a Conserved and Essential Element of Telomerase RNA

Abstract: Telomerase copies a short template within its integral telomerase RNA onto eukaryotic chromosome ends, compensating for incomplete replication and degradation. Telomerase action extends the proliferative potential of cells, and thus it is implicated in cancer and aging. Nontemplate regions of telomerase RNA are also crucial for telomerase function. However, they are highly divergent in sequence among species, and their roles are largely unclear. Using in silico three-dimensional modeling, constrained by mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 40 publications
3
109
0
Order By: Relevance
“…The structure is phylogenetically supported (Supplemental Fig. 1), however, mutations in this region in the context of larger yeast telomerase RNAs have resulted in only a slight decrease in activity in vivo and in vitro (Lin et al 2004;Shefer et al 2007;Qiao and Cech 2008). These base triples have been previously proposed based on thermodynamic characterization and were observed in Kluyveromyces lactis (Liu et al 2012;Cash et al 2013) and their main function is likely to favor pseudoknot formation and stability without directly contributing to catalysis.…”
Section: Resultsmentioning
confidence: 88%
“…The structure is phylogenetically supported (Supplemental Fig. 1), however, mutations in this region in the context of larger yeast telomerase RNAs have resulted in only a slight decrease in activity in vivo and in vitro (Lin et al 2004;Shefer et al 2007;Qiao and Cech 2008). These base triples have been previously proposed based on thermodynamic characterization and were observed in Kluyveromyces lactis (Liu et al 2012;Cash et al 2013) and their main function is likely to favor pseudoknot formation and stability without directly contributing to catalysis.…”
Section: Resultsmentioning
confidence: 88%
“…Finally and most importantly, conservation among functional domain sequences or structures provided additional confidence for the structure prediction. For example, the NMR structure of the hTR showed extensive tertiary interactions between the loop and stem nucleotides, rendering an essential triple helix in the pseudoknot structure [70,71]. A similar structure could possibly form in TbTR pseudoknot (Figure 6C).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the human, K. lactis, S. cerevisiae, and ciliate pseudoknots were proposed to contain U-AÁU base triples (Theimer et al 2005;Ulyanov et al 2005Ulyanov et al , 2007Shefer et al 2007;Qiao and Cech 2008). Given the low sequence conservation among the Candida spp.…”
Section: Pseudoknotmentioning
confidence: 99%
“…Several conserved elements were found to contribute crucial functions such as specifying the template boundary (Tzfati et al 2000;Seto et al 2003) or recruiting Est1, the yKu complex, and the Sm proteins (Seto et al 1999(Seto et al , 2002Peterson et al 2001). A unique pseudoknot element containing a major-grove triple-helix is crucial for K. lactis, S. cerevisiae, and human telomerase function (Theimer et al 2005;Shefer et al 2007;Qiao and Cech 2008). It was recently suggested that the triple helix functions in positioning the 39 end of the telomere at the catalytic site (Qiao and Cech 2008).…”
Section: Introductionmentioning
confidence: 99%